Expression profile of a novel glutathione S-transferase gene in the marine polychaete Perinereis aibuhitensis in short-term responses to phenanthrene, fluoranthene, and benzo[α]pyrene. (August 2021) - Yuan, Xiutang; Zhao, Huan; Wang, Yinan; Wang, Lili; Li, Dongmei; Zhang, Anguo; Yang, Xiaolong; Ma, Xindong; Yang, Dazuo; Zhou, Yibing
Abstract: Polychaete worms can eliminate polycyclic aromatic hydrocarbons (PAHs) in environments through a mechanism that increases their water solubility. This detoxification starts with cytochrome P450 enzymes (CYPs) and then with glutathione S-transferases (GSTs). Here, a novel GST gene was identified and characterized from the widespread polychaete Perinereis aibuhitensis . The full-length cDNA of GST is 1544 bp and encodes 256 amino acids, belonging to the omega class. Gene expression patterns in P . aibuhitensis showed that its transcriptional level was positively correlated with the concentration of benzo[α]pyrene (0.5, 2, 4, and 8 μg/L) exposure but was negatively correlated with a PAH benzene ring after it was exposed to the same mass concentrations of fluoranthene (3.2 μg/L), phenanthrene (2.9 μg/L), and benzo[α]pyrene (4.0 μg/L) during the 14-day experimentation. These findings indicate that omega GST may play an important role in the phase II detoxification of PAHs in polychaete worms, and the persistence and bioavailability of PAHs may depend on benzene rings. Highlights: A novel GST gene was identified from polychaete P . aibuhitensis . GST is 1544 bp, encodes 256 amino acids and belongs to omega class. Its transcriptional level was positively correlated with the concentration of B[α]P. But negatively correlated with benzene ring exposed to same mass concentrations of Flu, Phe, and B[α]P The bioavailability of PAHs may depend on the benzene rings.